Microsoft Office 2000 : illustrated introductory - Friedrichsen, Lisa.; Reding, Elizabeth Eisner.; Swanson, Marie L.; Beskeen, David W. (Course Technology, 2000)
This book presents about: Microsoft Word; Microsoft Excel; Microsoft PowerPoint; Microsoft Outlook; Microsoft Publisher & Microsoft Frontpage.